From Kothari Commission to Contemporary System of School Education : Challenges in Attaining Parental Involvement in Children’s Education - Gupta, Achala (Voices of Teachers and Teacher Educators, 2016)
The parent-teacher relationship has emerged as a topic of deliberation in the contemporary scholarship on education in India. Although latest policy documents indicate parental involvement as a necessary strategy for educational development, the inclusion of parents in schools’ affair is relatively recent development in education practices. The delay in perceiving parents as a crucial participant in schooling experience of a child makes it imperative to get to the root of education planning and its development. This paper, based on a discourse analysis of Kothari commission’s report, reviews how the home-school relationship or parent-teacher interaction were construed in one of the foundation documents in the history of modern education in India. Through attempting to understand commission’s views on the role of parents in children’s schooling and relating those perspectives with prevalent and contemporary education practices of education, the paper argues that there is a dire need for creating space for parents in order to achieve active engagement of parents in children’s schooling experience.